A SET OF PREVENTIVE MEASURES AGAINST CARIES IN CHILDREN WITH TYPE 1 DIABETES - Makhsumova I. Sh.; Dalimova K. Kh.; Zufarova D. S.; Karimova M. K. (Modern American Journals, 2025)
The article is a literary review devoted to the prevention of tooth decay in children with type 1 diabetes mellitus.The data of foreign, russian and uzbek literature has been studied using scientific search library databases: PubMed, Elibrary. The literature analysis was conducted based on 20 sources. The conducted analysis of literature data on issues of early diagnosis of caries in children and adolescents shows that this topic does not lose its relevance.
Keywords: Caries, childhood and adolescent diabetes, humoral and local oral immunity, immunometabolic disorders